2019
DOI: 10.1007/s10843-018-0242-7
|View full text |Cite
|
Sign up to set email alerts
|

When are innovativeness and responsiveness effective in a foreign market?

Abstract: Good managerial understanding of the mechanisms underlying the effectiveness of entrepreneurial orientation (EO) and market orientation (MO) in dynamic foreign markets improves the international competitiveness of the entire firm. Drawing on the dynamic capability view, this study contributes to the international strategy and entrepreneurship literature by extending our understanding of the actionable components of the EO/MO of firms' foreign units, that is, innovativeness and responsiveness. The study examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 99 publications
2
16
0
1
Order By: Relevance
“…They also responded to the calls of Covin & Miller (2014) and Wales (2016), who have reiterated the need for qualitative studies to refine the insight into EO manifestation within the organization, which has an impact on the performance of international ventures. Furthermore, our findings meet several scholars’ inquiries for investigating EO impact on foreign market performance in a disaggregated manner as they have a diverse impact (Dai et al , 2014; Pehrsson, 2019; Pehrsson, 2016; Shan et al , 2016). The present research has also responded to the inquiry of SMEs’ strategic orientation and export success in international business (Knight et al , 2020).…”
Section: Theoretical Implicationssupporting
confidence: 83%
See 1 more Smart Citation
“…They also responded to the calls of Covin & Miller (2014) and Wales (2016), who have reiterated the need for qualitative studies to refine the insight into EO manifestation within the organization, which has an impact on the performance of international ventures. Furthermore, our findings meet several scholars’ inquiries for investigating EO impact on foreign market performance in a disaggregated manner as they have a diverse impact (Dai et al , 2014; Pehrsson, 2019; Pehrsson, 2016; Shan et al , 2016). The present research has also responded to the inquiry of SMEs’ strategic orientation and export success in international business (Knight et al , 2020).…”
Section: Theoretical Implicationssupporting
confidence: 83%
“…Therefore, many studies called for further research on the impact of EO on firm performance (Pehrsson, 2019; Rua et al , 2017; Knight, Moen, & Madsen, 2020). In the context of methodology, several studies suggested that EO dimensions’ nature on firm performance is vital to explore EO and SMEs’ internationalization (Miller, 2011; Jones et al , 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Based on theoretical roots anchored in the notion of matching firms' strategic orientation, traits and capabilities with those required by the environment in which they operate, we use the dominant logic (Prahalad and Bettis 1986) and adaptation (Chakravarthy 1982) frameworks, to propose that the effectiveness of EO in foreign market entry depends on the degree to which the traits that reflect a strong EO are beneficial to the entry. Furthermore, the notion that a strong EO imbues firms with a greater capacity to modify their capabilities and better align them with the market is consistent with the premise that EO is a dynamic capability (Jantunen et al 2005;Pehrsson 2019).…”
Section: Introductionsupporting
confidence: 65%
“…Market responsiveness is crucial to a company's performance because it manifests the firm's strategies in foreign markets and are actionable (Cadogan, 2012). Pehrsson (2019) demonstrates that market-driven responsiveness is an actionable component of strategic orientations that affect performance. The ability of an organisation to quickly respond to customers' needs and demands enhances customer satisfaction, and thereby is a value-creation capability critical for sustained competitive advantage.…”
Section: Market Responsivenessmentioning
confidence: 99%